2009
DOI: 10.1517/14728220902942322
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and the pathogenesis of age-related macular degeneration

Abstract: It is now well-known that AMD is a multi-factorial disease, with environmental causes and genetics all playing a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 48 publications
0
43
1
Order By: Relevance
“…Inflammation and angiogenesis play pivotal roles in CNV, the major cause of vision loss in patients with AMD (39,40). Our results show that miR-23∼27∼24 cluster members are up-regulated in CNV (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Inflammation and angiogenesis play pivotal roles in CNV, the major cause of vision loss in patients with AMD (39,40). Our results show that miR-23∼27∼24 cluster members are up-regulated in CNV (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…The role of inflammation has been given much consideration [20], even if the nature of the immune cell interactions that drive cellular and tissue changes in AMD is still not fully understood [21]. …”
Section: Discussionmentioning
confidence: 99%
“…33 Dramatic advances have been made in unraveling the biological bases of AMD, implicating chronic local inflammation and activation of the complement cascade in the pathogenesis of the condition. 16,17 A number of complement system proteins, complement activators and complement regulatory proteins were identified as molecular constituents of drusen, the hallmark extracellular deposits associated with early AMD 12,[39][40][41][42] and of geographic atrophy and choroidal neovascularization, the hallmark of advanced AMD. 43 Genetic studies revealed highly significant associations between AMD and variants of several complement pathway-associated genes, including complement factor H, complement factor H-related 1 and 3, complement factor B, complement component 2 and complement component 3.…”
Section: Discussionmentioning
confidence: 99%
“…10 Inflammation has recently received some attention as a potential risk factor for AMD. [11][12][13][14][15][16][17][18][19][20][21][22] Immunological changes seemed to be related to early pathological changes in retinal pigment epithelial (RPE) and drusen formation. Immune components, including immunoglobulins, complement factors and fibrinogen, have been observed to be entrapped within drusen.…”
Section: Introductionmentioning
confidence: 99%